Synthesis of nano-α mangostin based on chitosan and Eudragit S 100 - Herdiana, Yedi (J Adv Pharm Technol Res, 2020)
Alpha-mangostin is a xanthone compound isolated from the mangosteen plant (Garcinia mangostana L.), which has various pharmacological activities. However, in its utilization alpha-mangostin is unstable and shows low solubility in the oral delivery system. Nanoparticles can deliver specific drugs to their workplace and increase the solubility. The objectives of this study were to create and characterize the alpha-mangostin nanoparticles based on chitosan and Eudragit® S 100. The nanoparticles were made by the ionic gelation method with comparisons core: Coating FI (1:2), FII (1:1), and FIII (2:1). Nanoparticles powder obtained using the spray pyrolysis method. Characterization using Fourier transform infrared indicates that the nanoparticles have been coated properly, and no damage occurred in the formula. The particle sizes for FI, FII, and FII are 373.381 ± 138.023 nm, 398.333 ± 184.977 nm, and 326.567 ± 130.366 nm, respectively, with a smooth surface. The entrapment efficiency value of FI, FII, and FIII are, respectively, 99.7692%, 99.6535%, and 99.476%. Alpha-mangostin was successfully encapsulated in chitosan-tripolyphosphate polymer by ionic gelation method and then coated with Eudragit S 100. Alpha-mangostin chitosan-eudragit nanoparticles (core: Polymer ratio of 1:2) yielded more entrapment efficiency.